An Algebraic Method to Determine the Local Field of Condensed System (Journal of Atomic and Molecular Sciences, 2015)
An algebraic method is proposed to generate a self-consistent convergedcomplex polarizability of atoms and molecules from limited available data. An iterativemethod is also suggested to generate the general accurate local field models ofcondensed systems. The effect of the local fields on the photoabsorption cross sectionsas the functions of the media density and structures has been studied in the presentwork. A substantial influence on the photoabsorption cross section has been foundwhen the media density exceeds a critical density in the present unique model.